Comparative physiological and transcriptomic analyses identify computationally predicted key genes and regulatory pathways in non-heading Chinese cabbage under heat stress - Wei Liu; Zhangyang Dai; Jingyi Jia; Xiaofeng Li; Hongfang Zhu; Xianzhao Kan; Bo Zhu (BMC Plant Biology)
Abstract Background Non-heading Chinese cabbage (Brassica campestris (syn. Brassica rapa) ssp. chinensis) (NHCC) is an important vegetable crop with economic benefits and is widely cultivated worldwide. Heat stress disrupts intracellular homeostasis, resulting in significant growth inhibition of buds and roots, severe retardation of growth and development, and even death. However, there are relatively few studies on the molecular response mechanism of NHCC to heat stress. Results In this study, RNA sequencing (RNA-seq) technology was employed to investigate the transcriptome data of the heat-tolerant variety “SHI” and the heat-sensitive variety “aijiaohuang” (“AJH”) under high temperature. Differentially expressed genes (DEGs), including transcription factors (TFs), genes related to hormone synthesis, and genes related to protein processing in the endoplasmic reticulum, were identified in both varieties. The combination of multi-sample RNA-seq data and weighted gene co-expression network analysis (WGCNA) identified four key modules, namely the darkgreen module, the yellow module, the blue module, and the turquoise module, and core genes within them, including MYB-related, HSP20 and DBB etc., were mined. Conclusion Our findings suggest that protein processing in the endoplasmic reticulum, photosynthesis, and plant hormone signaling are crucial for “SHI"’s response to heat stress and some candidate genes such as MYB-related, HSP20 and DBB were identified. We validated our results with qRT-PCR, reinforcing the reliability of our data. These insights deepen our understanding of the physiological and molecular bases of NHCC heat tolerance and identify key genes for further molecular investigation.